Activity of red wine polyphénol on endothelial no-synthase - NAGUIBOU, Djibril; ATTAKPA, S. EUGÈNE; GANFON, M. Y. HABIB; OMOREGBE, VICTOR Bruno (My University, 2016)
Polyphenols (PPH) represent a group of chemical substances found in plants, characterized by the presence of more than one phenol unit. The largest and best studied polyphenols are the flavonoids. Polyphenols contained in red wine have beneficial effects on cardiovascular health. The aim of our research was a comparative and interactive study of four red wine polyphenols - resveratrol (R), quercetin (Q), kaempferol (K) and isorhamnetin (IH) which may have a long term properties as the increase of (NO) synthase expression, acting on the prometer activity when used alone or in equimolar mixtures. To determine their activity, we performed a luciferase reporter gene assay on EA.hy926 cells stably transfected with a luciferase reporter gene construct containing eNOS promoter. The Bradford assay was also performed to evaluate the cytotoxicity and the differences in cell number. The median effect equation, as an interaction analysis evaluating synergy or antagonism of the combinations was done according to the principle of mass-action law and the dose reduction index (DRI) was calculated for all mixtures. All single polyphenols activated eNOS promoter. The EC50 values were in micromolar concentrations ranging from 3.44 μM (R2 = 0.96) for kaempferol to 9.89 μM for isorhamnetin (R2 = 0.94). All mixtures activated eNOS promoter, but their interactions varied from synergy (Q+R, Q+IH+K, Q+R+K and Q+R+IH+K), through additive (R+IH+K) to antagonistic interaction (R+IH, R+K, Q+IH, Q+K, IH+K and R+Q+IH). In this study, we show for the first time that red wine polyphenols activated eNOS promoter when used alone and in mixtures with different types of interactions.
Keywords: Polyphenols; eNOS promoter; luciferase reporter gene assay; interaction analysis.